Beckman Facilities, Netherlands (1968)
The Amsterdam photograph (2012-002_1157) is dated to 1968; the Mijdrecht photograph (2012-002_1158) is undated.
Keywords: Buildings; Parking lots; Automobiles; Beckman Instruments, Inc.